ANALYSIS OF THE ROLE OF FUTURISTIC LEADERSHIP STYLE AND TEACHER COMPETENCY ON SCHOOL QUALITY PERFORMANCE THROUGH THE IMPLEMENTATION OF SCHOOL-BASED MANAGEMENT AT SMPN IN JEMBER REGENCY - Kristatiningsih, Dwi; Qomariah , Nurul; Hermawan, Haris (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: The aim of this research is to examine the effect of futuristic leadership style and teacher competency on the quality school quality performance of State Middle Schools in Jember Regency, both directly and indirectly through the implementation of school-based management. Methods: This research uses quantitative research methods with descriptive problem formulation. This research was conducted in Jember Regency and at the time of this research the location of the Jember Regency Education Office was Jl. Dr. Subandi No. 29 Jember by taking data from 94 State Middle Schools in Jember district. The population of this study were all principals of state junior high schools in Jember Regency and the sampling method used the Saturated Sampling technique. The data analysis technique used is Partial Least Square (PLS) which is processed with WarpPLS software. Results: The research results show that futuristic leadership style and teacher competency has significant effect on the implementation of school-based management. Futuristic leadership style and teacher competency has significant effect on school quality school quality performance. The implementation of school-based management has significant effect on school quality school quality performance. The futuristic leadership style has significant effect on school quality school quality performance through the implementation of school-based management, while teacher competency has insignificant effect on school quality school quality performance through the implementation of school-based management. Novelty: This research offers novelty in aspects of the research model related to the antecedents of school quality school quality performance which involves a futuristic leadership style and teacher competency mediated by the implementation of school-based management.